Considerations in the evaluation and management of oral potentially malignant disorders during the COVID‐19 pandemic - Shanti, Rabie M. (Head Neck, 2020)
AIM: The COVID‐19 pandemic has resulted in society experiencing unprecedented challenges for health care practitioners and facilities serving at the frontlines of this pandemic. With regard to oral cancer, there is a complete absence of literature regarding the long‐term impact of pandemics on patients with oral potentially malignant disorders (OPMDs). The objective of this article is to put forth an institutional multidisciplinary approach for the evaluation and management of OPMDs. METHODS: A multidisciplinary approach was put formalized within our institution to risk stratify patients based on need for in‐person assessment vs telehealth assessment during the COVID‐19 pandemic. RESULTS: With judicious risk stratification of patients based on clinical features of their OPMD and with consideration of ongoing mitigation efforts and regional pandemic impact, providers are able to safely care for their patients. CONCLUSIONS: The COVID‐19 pandemic has required health care practitioners to make novel decisions that are new to us with development of creative pathways of care that focused on patient safety, mitigation efforts, and clinical management of disease processes. The care of patients with OPMDs requires special considerations especially as patients at high risk for severe COVID‐19 illness are also higher risk for the development of OPMDs.